Review Of Completeness Of Medical Records Related To The Settlement Of Health Insurance Claims To Improve The Quality Of Services At RSIA Artha Mahinrus - Johanna Christy; Marta Simanjuntak; Nila Sari; Nurzia Raihana (Jurnal EduHealth, 2023)
Medical Records are facts related to the patient's condition, medical history, treatment, past, and currently written by a health professional who provides good services. The purpose of this study was to determine the completeness of medical record files related to insurance claims in order to improve hospital services. The type of research used by the researcher is the type of quantitative research, which is a research method based on the philosophy of positivism. The sample in this research is part of the inpatient medical record file at RSIA Artha Mahinrus. So the number of samples in this study were 51 medical record files. The completeness of inpatient medical record files, 92% complete files and 8% incomplete files, of 51 medical record files. The percentage of completeness of the contents of the medical resume for making incomplete claims, namely data entry and exit dates is 2%, supporting examination is 4%, and action is 2%. The recording of medical records in this study can be categorized as good, because currently the completeness of the medical record files reaches 92%, it can be stated that the quality of medical record services is good.